Pathway to hepatitis C elimination: insights from a large tertiary hospital in South China - Suling Chen; Yuyuan Xu; Bing Li; Tao Yu; Xiaoxuan Wu; Yuanhui Jiang; Hongjie Chen; Xuwen Xu; Jie Peng; Shaohang Cai (Annals of Medicine)
Background Although the introduction of direct-acting antiviral drugs (DAAs) has greatly enhanced the prognosis for hepatitis C, the timely diagnosis and treatment of hepatitis C virus (HCV) infection remain a severe challenge in China.Methods This retrospective study involved 368,577 patients tested for hepatitis C antibodies from 2020 to 2023 at a large tertiary hospital in South China. It primarily focused on analyzing the prevalence of Anti-HCV and HCV RNA and further evaluated the impact of the ‘Hepatitis C-Free Hospital’ initiative.Results Between 2020 and 2023, this large tertiary hospital in South China reported an overall Anti-HCV positivity rate of 1.08%, with males (1.06%) higher than females (0.57%). In particular, the highest rates were observed in males aged 40-49 (2.24%) and females aged 60-69 (1.00%). There was a gradual decline in the Anti-HCV positivity rate over time. As for HCV RNA testing, it indicated an overall positivity rate of 30.95%, more prevalent in males. Significantly, the ‘Hepatitis C-Free Hospital’ initiative increased HCV RNA testing and treatment completion rates, with sustained virological response (SVR) rates escalating from 92.86% to 99.61%.Conclusions This study identified specific patient groups with high HCV positivity rates. Additionally, the ‘Hepatitis C-Free Hospital’ initiative significantly increased HCV RNA testing and treatment rates, providing a feasible model for regional HCV elimination.